Evaluating the Extent of Clinical Variability Among Treatment Options for Patients With Adult Spinal Deformity. Issue 7 (August 2017) - Phan, Philippe; Ploumis, Avraam; Hess, Kathryn; Wood, Kirkham B.
Abstract : Study Design: This is a surgical strategy survey. Objective: The purpose of this study was to evaluate the variability in in surgical strategy planning of adult spinal deformity (ASD) based on patients' clinical and radiographic data. Background: Literature guiding the management of ASD consists primarily of studies with low levels of evidence. Recent studies have demonstrated good agreement among surgeons about the factors influencing surgical decision but poor agreement about the need for surgery. Therefore there is a relative lack of consensus and guidelines in the clinical practice and treatment of ASD. Methods: A total of 28 adult deformity surgeons were asked to fulfill an online survey of 10 spinal deformity cases. Case presentation included a clinical vignette with photographs, Oswestry Disability Index and Visual Analog Scale scores and imaging with radiographic measurements. For each case, the surgeons were asked whether surgical management would be beneficial and if so, their surgical plan (approach, staging, need for fusion, osteotomy or decompression and the techniques used). Intraobserver and interobserver reliability were studied using average Cohen and Feiss Kappa statistics, respectively. Descriptive statistics were calculated to evaluate the frequency of each of the alternatives in surgical planning. Results: Average intrarater and interrater agreement for surgical strategy were evaluated to be substantial (κ=0.62) and fair (κ=0.24), respectively. Detailed interrater statistics demonstrates that there was only slight agreement on the need for surgery (κ=0.15), the approach (κ=0.15), and the need for fusion (κ=0.16) while moderate agreement was reached for the need for decompression (κ=0.42) and osteotomy (κ=0.29). Conclusions: Among surgeons, agreement about the need for surgery and the surgical strategy for ASD is limited. Findings from this survey highlight the need for comprehensive classifications for ASD, higher-level studies including randomized trials to set guidelines and lessen the variability in clinical practices, which would then hopefully lead to improved outcomes.